Phytochemical and in vitro anthelmintic properties of mesocarp of fruit extracts from Balanites aegyptiaca (L.) Delile (Zygophyllaceae) - Mohamed Bonewendé Belemlilga; Félicité Moyenga; Abdoul Gilchrist Laurent Boly; Hippolyte Ouédraogo; Souleymane Compaoré; Jules Yoda; Estelle Noëla Hoho Youl; Félix Bondo Kini; Sylvin Ouédraogo; Aristide Traoré (Shahrekord University of Medical Sciences, 2024)
Introduction: Balanites aegyptiaca L. (DEL) is a plant used in Burkina Faso in traditional medicine to treat gastrointestinal parasitosis. The purpose of this study was to assess the in vitro anthelmintic activity of aqueous and hydro-ethanolic macerates (AM and HEM) of the fruit mesocarp from Balanites aegyptiaca against Haemonchus contortus. Methods: Phytochemical screening of the extracts was done using thin-layer chromatography. The egg hatch inhibition assay (EHIA) at 0.125, 0.15, 0.25, 0.625, 1.25, and 5 mg/mL and Adult worms mortality assay (AWMA) at 0.625, 1.25, 2.5, 5, 10, and 15 mg/mL concentrations were evaluated. Albendazole and levamisole were used as standards, and phosphate-buffered saline was used as a negative control. The antioxidant potential of extracts was evaluated using the ABTS [2,2'-azinobis (3-ethyl benzoin-6-sulphonate)] and DPPH (2,2-diphenyl-picrylhydrazine) methods and Fe3+ ion reducing power. The standards used were trolox and ascorbic acid. Results: Several secondary metabolites such as sterols, triterpenes, tannins, flavonoids, coumarins, and saponins were identified. For EHIA, the AM was more effective than HEM with 50% inhibitory concentrations (IC50) of 0.35 mg/mL and 0.43 mg/mL, respectively. AM was even more effective for AWMA than HEM, with 50% lethal concentrations (LC50) of 3.15 mg/mL and 8.37 mg/mL, respectively. The DPPH method gave an IC50 of 834.55 μg/mL and the capacity to reduce ferric ion (Fe3+) to ferrous ion (Fe2+) was 270.4 µmol/Ascorbic acid equivalent. Conclusion: AM and HEM from the mesocarp of B. aegyptiaca have anthelmintic properties. AM is more effective than HEM, which justifies their use with priority for AM.